PENGEMBANGAN MODEL MODIFIKASI PERILAKU SOSIAL MELALUI MEDIA BELAJAR BERKONSEP KONVERGENSI BAGI ANAK AUTIS - Suparno, Suparno (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2011)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>The study is aimed at developing a model of social behaviour modifaction through a convergence-based learning media for autistic children at special schools. More specifically, the study is to describe (1) conditions and characteristics of autistic children, (2) competencies for language, academic, and pre-academic, and (3) development of the modification media. The study is developmental in two phases, namely (1) pre-development, and (2) development. The subjects are 10 autistic children from Bina Anggita special schools and leading special schools in the province chosen through purposive sampling by grade levels and class activities. The pre-development data are collected through observation and interviews; the development data through theoretical analysis and pre-research. Data are analyzed by a descriptive qualitative technique. Findings show (1) in the pre-development, subjects are (a) able to do a short eye contact, (b) have low pre-academic and academic conditions, and (c) not able to keep eye contact for five seconds, tend to have tantrums, weep for no reason, laugh, self-stimulate, mumble, and have short attention span; (2) convergence-based hypothetical plan for development steps: (a) assessment of social behaviours, (b) development of learning themes and sub-themes, (c) design of convergence-based learning media, (d) procedures of social behaviour modification merged in learning activities, and (e) monitoring and evaluation of outcomes of the subjects’ behaviour changes